Antioxidant Capacity and Phytochemical Profile of Crescentia cujete L. Fruit Peel Extract from The Serang Region - Purnamasari, Mayshah (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Crescentia cujete is a plant commonly found in the Serang region; however, its fruit peel remains largely underutilized, and studies regarding its bioactivity potential are minimal. This research utilized dried, pulverized C. cujete fruit peel, which was extracted using the Soxhlet method with 96% ethanol to yield the ethanolic extract. Qualitative phytochemical screening was conducted to identify the secondary metabolite classes . Antioxidant capacity was measured using ABTS•⁺ radicals, and DPPH values were expressed as IC₅₀. Phytochemical results showed the presence of flavonoids, phenols, alkaloids, terpenoids, steroids, and saponins. The DPPH assay yielded a high IC50 value of 1166.68 ppm, classifying the extract as having very weak antioxidant activity. Conversely, the TEAC method demonstrated high antioxidant capacity, yielding a value of 171.37+4.03 mM TE/g. The significant difference between the two methods suggests that antioxidant effectiveness is strongly influenced by the radical and chemical properties of the constituent compounds. The novelty of this study lies in the comparative evaluation of the antioxidant activity of C. cujete fruit peel using two different radical systems and in the finding that the extract exhibits selective, strong activity against the ABTS radical. C. cujete fruit peel is potentially a source of natural antioxidants.